Vibration fatigue study of the helical spring in the base-excited inerter-based isolation system. (September 2019) - Čakmak, D.; Tomičević, Z.; Wolf, H.; Božić, Ž.; Semenski, D.; Trapić, I.
Abstract: The aim of this study is to analytically and numerically model the vibration-induced helical spring fatigue in a generalized vibration isolation system. The system consists of a receiving body and a dynamically active base coupled through a passive isolator. The isolator consists of a coupling helical spring and an inerter. System inherent damping is considered through modal damping. Vibration isolation system is analysed parametrically by varying its corresponding dimensionless coefficients. The coupling helical spring fatigue life extension is used as the isolation quality criterion. Since isolator spring stress and related fatigue life directly correspond to relative displacement between spring terminals, the effect of inerter on relative displacement amplitudes is determined. Novel helical spring stress and deflection correction factors are proposed based on the theory of elasticity and finite element analysis results. The proposed helical spring correction factors are more accurate compared to correction factors available in the current literature, especially when considering very large pitch angles. Fatigue life improvement of considered helical spring is achieved due to introduction of inerter in the isolator system, which is especially evident in the resonant working conditions. Highlights: Analytical and numerical study of the vibration-induced helical spring fatigue. Helical spring fatigue life improvements due to inerter in the isolator. Novel more accurate spring stress and deflection correction factors proposed. Detailed analytical and finite element method benchmark example presented. Procedure can be used for assessment of vibration fatigue in suspension systems.